2008
DOI: 10.1128/ec.00038-08
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen-Activated Protein Kinase Hog1 Mediates Adaptation to G1Checkpoint Arrest during Arsenite and Hyperosmotic Stress

Abstract: Cells slow down cell cycle progression in order to adapt to unfavorable stress conditions. Yeast (Saccharomyces cerevisiae) responds to osmotic stress by triggering G 1 and G 2 checkpoint delays that are dependent on the mitogen-activated protein kinase (MAPK) Hog1. The high-osmolarity glycerol (HOG) pathway is also activated by arsenite, and the hog1⌬ mutant is highly sensitive to arsenite, partly due to increased arsenite influx into hog1⌬ cells. Yeast cell cycle regulation in response to arsenite and the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 32 publications
2
30
0
Order By: Relevance
“…Hog1, the canonical MAPK of the HOG pathway, has been shown to be involved in G1 progression (Belli et al, 2001). This conclusion is in agreement with a prolonged G1 arrest observed in hog1 mutants after osmotic challenge (Migdal et al, 2008). Hog1 phosphorylates the CDK inhibitor Sic1, reducing the expression of the CLN1 and CLN2 cyclins and, consequently preventing cell cycle progression upon osmotic challenge (Escoté et al, 2004).…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…Hog1, the canonical MAPK of the HOG pathway, has been shown to be involved in G1 progression (Belli et al, 2001). This conclusion is in agreement with a prolonged G1 arrest observed in hog1 mutants after osmotic challenge (Migdal et al, 2008). Hog1 phosphorylates the CDK inhibitor Sic1, reducing the expression of the CLN1 and CLN2 cyclins and, consequently preventing cell cycle progression upon osmotic challenge (Escoté et al, 2004).…”
Section: Introductionsupporting
confidence: 91%
“…Hog1 has also an important role in G2 phase through stabilization of Swe1, a protein kinase which needs to be degraded for cell cycle progression to occur (Clotet et al, 2006). In addition to osmotic stress, exposure to arsenite also leads to a Hog1-dependent G1 and G2 delay (Migdal et al, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…Thus, by using the HOG1 deletion mutant ( hog1 Δ) only, we could not pin-point neither time nor mechanism of Hog1 action during G 1 cell cycle delay and recovery. Nevertheless, we showed with an analogue-sensitive mutant of Hog1 (Hog1-as) and 1-NM-PP1 inhibitor, that lack of Hog1 kinase activity is responsible for persistent G 1 arrest in the presence of As(III) [20]. However, the results of the cell cycle experiments with the Hog1-as allele were confounded by the fact that in the absence of 1-NM-PP1, the Hog1-as strain displayed much longer As(III)-induced G 1 delay than wild-type cells [14], [20].…”
Section: Resultsmentioning
confidence: 98%
“…It has been reported that As(III) delays the budding yeast cell cycle in all phases [16] and induces phosphorylation of the Rad53 checkpoint kinase (CHK2 in humans) [17]. Importantly, several genome-wide screens have revealed that deletion of yeast genes encoding proteins involved in sensing and repairing of DNA damage, e.g.…”
Section: Introductionmentioning
confidence: 99%